Randomized Phase III Trial of Ibrutinib and Rituximab Plus Cyclophosphamide, Doxorubicin, Vincristine, and Prednisone in Non-Germinal Center B-Cell Diffuse Large B-Cell Lymphoma - Younes, Anas; Sehn, Laurie H; Johnson, Peter; Zinzani, Pier Luigi; Hong, Xiaonan; Zhu, Jun; Patti, Caterina; Belada, David; Samoilova, Olga; Suh, Cheolwon; Leppä, Sirpa; Rai, Shinya; et al. (Journal of clinical oncology, 2019)
PURPOSE: Ibrutinib has shown activity in non-germinal center B-cell diffuse large B-cell lymphoma (DLBCL). This double-blind phase III study evaluated ibrutinib and rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in untreated non-germinal center B-cell DLBCL. PATIENTS AND METHODS: Patients were randomly assigned at a one-to-one ratio to ibrutinib (560 mg per day orally) plus R-CHOP or placebo plus R-CHOP. The primary end point was event-free survival (EFS) in the intent-to-treat (ITT) population and the activated B-cell (ABC) DLBCL subgroup. Secondary end points included progression-free survival (PFS), overall survival (OS), and safety. RESULTS: A total of 838 patients were randomly assigned to ibrutinib plus R-CHOP (n = 419) or placebo plus R-CHOP (n = 419). Median age was 62.0 years; 75.9% of evaluable patients had ABC subtype disease, and baseline characteristics were balanced. Ibrutinib plus R-CHOP did not improve EFS in the ITT (hazard ratio [HR], 0.934) or ABC (HR, 0.949) population. A preplanned analysis showed a significant interaction between treatment and age. In patients age younger than 60 years, ibrutinib plus R-CHOP improved EFS (HR, 0.579), PFS (HR, 0.556), and OS (HR, 0.330) and slightly increased serious adverse events (35.7% v 28.6%), but the proportion of patients receiving at least six cycles of R-CHOP was similar between treatment arms (92.9% v 93.0%). In patients age 60 years or older, ibrutinib plus R-CHOP worsened EFS, PFS, and OS, increased serious adverse events (63.4% v 38.2%), and decreased the proportion of patients receiving at least six cycles of R-CHOP (73.7% v 88.8%). CONCLUSION: The study did not meet its primary end point in the ITT or ABC population. However, in patients age younger than 60 years, ibrutinib plus R-CHOP improved EFS, PFS, and OS with manageable safety. In patients age 60 years or older, ibrutinib plus R-CHOP was associated with increased toxicity, leading to compromised R-CHOP administration and worse outcomes. Further investigation is warranted.
Keywords: pyrazoly; Adenine; Vincristine; Humans; Placebos; lidé středního věku; pyrimidiny; Double-Blind Method; doxorubicin; Aged; mladý dospělý; dospělí; protokoly protinádorové kombinované chemoterapie; Female; Doxorubicin; Prednisone; senioři; dvojitá slepá metoda; lidé; doba přežití bez progrese choroby; Piperidines; placebo; Adult; prednison; adenin; ženské pohlaví; Kaplanův-Meierův odhad; Male; rituximab; difúzní velkobuněčný B-lymfom; vinkristin; Middle Aged; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; Cyclophosphamide; Lymphoma, Large B-Cell, Diffuse; Rituximab; Young Adult; senioři nad 80 let; Progression-Free Survival; Kaplan-Meier Estimate; piperidiny; míra přežití; Pyrimidines; mužské pohlaví; Pyrazoles; cyklofosfamid; Survival Rate